2013
DOI: 10.1016/j.nbd.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Altered short-term plasticity in the prefrontal cortex after early life seizures

Abstract: Seizures during development are a relatively common occurrence and are often associated with poor cognitive outcomes. Recent studies show that early life seizures alter the function of various brain structures and have long-term consequences on seizure susceptibility and behavioral regulation. While many neocortical functions could be disrupted by epileptic seizures we have concentrated on studying the prefrontal cortex (PFC) as disturbance of PFC functions is involved in numerous co-morbid disorders associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 69 publications
2
30
0
1
Order By: Relevance
“…This hypothesis has also been tested in rodents. Recurrent flurothyl seizures induced during the neonatal period lead to an increase in LTP in the somatosensory cortex and to increases in STP in the prefrontal cortex (Isaeva et al 2010;Hernan et al 2013). Similar effects on plasticity have also been identified following postnatal hypoxic seizures (Jensen 1999;Zhou et al 2011).…”
Section: The Impact Of Seizuresmentioning
confidence: 74%
“…This hypothesis has also been tested in rodents. Recurrent flurothyl seizures induced during the neonatal period lead to an increase in LTP in the somatosensory cortex and to increases in STP in the prefrontal cortex (Isaeva et al 2010;Hernan et al 2013). Similar effects on plasticity have also been identified following postnatal hypoxic seizures (Jensen 1999;Zhou et al 2011).…”
Section: The Impact Of Seizuresmentioning
confidence: 74%
“…However, mossy fiber sprouting occurs in adult animals 39,40,43. Extratemporal areas can also be affected, including increased prefrontal cortex thickness, synaptic plasticity alterations, and decreased behavioral flexibility 45,46. These data indicate substantial changes in prefrontal cortex function, which may be an important substrate of cognitive deficits in humans with a history of infant or juvenile seizures 45.…”
Section: Chemoconvulsantsmentioning
confidence: 99%
“…Previous work with this model showed that rats with ELS have persistent increased excitation (Isaeva et al 2010) and decreased GABA currents (Isaeva et al 2009) in the neocortex and a substantially reduced lower seizure threshold (Holmes et al 2015). ELS also have been shown to increase short-term plasticity in the mesial prefrontal cortex (mPFC) (Hernan et al 2013). Alterations in short-term plasticity in the mPFC have been associated with changes in hippocampal-PFC synchrony (Sigurdsson et al 2010;Fenelon et al 2013).…”
Section: Altered E/i Balance and Connectivitymentioning
confidence: 99%